2014
DOI: 10.5812/traumamon.14480
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors of Mortality in Burn Patients

Abstract: Background:Burn injuries impose a considerable burden on healthcare systems in Iran. It is among the top ten causes of mortality and a main cause of disability.Objectives:This study aimed to examine factors influencing mortality in burn patients admitted to the main educational tertiary referral hospital in Kermanshah.Patients and Methods:All patients admitted to the Imam Khomeini Hospital (from March 2011 to March 2012), due to thermal burn injuries were included in the study. We applied multiple logistic reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 31 publications
(34 reference statements)
0
14
0
Order By: Relevance
“…Using the opportunity sampling technique of all data for patients admitted to the burns unit throughout the period of January 2005 to December 2017, a total of 1,288 admissions to the burns unit were included in the study. Data included the demographics, cause and type of burns and the affected total body surface area (TBSA) which are considered major risk factors for burn morbidity and mortality (22)(23)(24)(25). Data preview was limited to the research team and for research purposes only.…”
Section: Methodsmentioning
confidence: 99%
“…Using the opportunity sampling technique of all data for patients admitted to the burns unit throughout the period of January 2005 to December 2017, a total of 1,288 admissions to the burns unit were included in the study. Data included the demographics, cause and type of burns and the affected total body surface area (TBSA) which are considered major risk factors for burn morbidity and mortality (22)(23)(24)(25). Data preview was limited to the research team and for research purposes only.…”
Section: Methodsmentioning
confidence: 99%
“…In another clinical study involving 4927 burn patients with an overall death of 5.3%, the mortality rate was approximately two-fold higher in women aged between 30 and 59 years compared to the same age group of male burn victims [ 161 ]. In fact, it has been shown that female gender is linked to a more detrimental outcome in the majority of clinical studies following burn trauma [ 6 , 162 , 163 , 164 ]. The reasons for adverse outcome in women are likely attributable to sex-specific differences in metabolic and neuroendocrine responses following burn injury [ 161 ].…”
Section: Other Biological Factors Related To Cardiac Dysfunction Amentioning
confidence: 99%
“…Previously conducted studies reported that the most common cause of death in patients with burns was flame burns. [4,21,[41][42][43] The pathogenesis of electrical burns has certain differences concerning the other types of burns (6). A study conducted on 964 patients in Iran by Aghazadeh et al [44] reported that death arose from scalding with flame, chemicals and hot liquid, respectively.…”
Section: Burning Aetiologymentioning
confidence: 99%